2012
DOI: 10.1016/j.aprim.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de la regulación de espacios sin humo en la exposición referida al humo ambiental de tabaco en Zaragoza

Abstract: The impact has been favourable, decreasing the exposure by more than 20%, with this fall being more marked in the population that currently define themselves as non-smokers. There is population support for the new legislation. Finally, there has been no observed fall in the frequency of visits to the same places.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In Spain, crosssectional studies in Galicia (a Northern Spanish region) and several primary care centers in Zaragoza city (Villaverde Royo et al, 2012;Perez-Rios et al, 2014) found a marked decrease in the SHS exposure of adults after the 2010 legislation. Nevertheless, more than 25% of the adults (16-74 yr) reported SHS exposure, predominantly at home.…”
Section: -2006 2011-2012mentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain, crosssectional studies in Galicia (a Northern Spanish region) and several primary care centers in Zaragoza city (Villaverde Royo et al, 2012;Perez-Rios et al, 2014) found a marked decrease in the SHS exposure of adults after the 2010 legislation. Nevertheless, more than 25% of the adults (16-74 yr) reported SHS exposure, predominantly at home.…”
Section: -2006 2011-2012mentioning
confidence: 99%
“…There has been some research into the effects of the 2010 Spanish anti-smoking law on SHS exposure in adults (Villaverde Royo et al, 2012;Perez-Rios et al, 2014;Sureda et al, 2014;Sánchez-Rodríguez et al, 2015). However, it is also important to establish whether the stricter smoking ban has had an impact on the reduction of exposure in children, by evaluating, for example, the cotinine load in this population.…”
mentioning
confidence: 97%